2020
DOI: 10.1186/s12884-020-03407-8
|View full text |Cite
|
Sign up to set email alerts
|

Immediate versus delayed induction of labour in hypertensive disorders of pregnancy: a systematic review and meta-analysis

Abstract: Background Mothers with hypertensive disorder of pregnancy can be managed with either immediate or delayed induction of labour with expectant monitoring of both mother and baby. There are risks and benefits associated with both the type of interventions. Hence, this review was conducted to compare outcomes of immediate and delayed induction of labour among women with hypertensive disorder of pregnancy based on disease severity and gestational age. Methods We conducted systematic searches in various databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Based on a systematic review [2,17], the benefit of expectant management is still unclear. Though expectant management resulted in pregnancy prolongation of approximately 7-15 days, perinatal mortality rate was comparable in some studies [4,7,9,16], including a large RCT reported by Vigil-De Gracia et al [7] in spite of 10-day prolongation, and slightly decreased in some studies [1,5,13,17]. Likewise, maternal morbidity was comparable in most studies [1,4,13,14] and increased in some studies [5,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a systematic review [2,17], the benefit of expectant management is still unclear. Though expectant management resulted in pregnancy prolongation of approximately 7-15 days, perinatal mortality rate was comparable in some studies [4,7,9,16], including a large RCT reported by Vigil-De Gracia et al [7] in spite of 10-day prolongation, and slightly decreased in some studies [1,5,13,17]. Likewise, maternal morbidity was comparable in most studies [1,4,13,14] and increased in some studies [5,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…In preeclampisa or eclampsia delivery seems to be the only definite therapy and stabilization of BP before operative birth is important for maternal complications. Immediate delivery could be one possible approach in women, especially beyond the 37 weeks of gestation [63], but so as the delayed delivery with expectant monitoring [64]. Especially for women with nonsevere hypertension, there is not a consensus regarding the timing of delivery.…”
Section: Treatment Of Hypertension During Pregnancymentioning
confidence: 99%
“…Latest data show that in case of late onset mild preeclampsia, the choice of expectant approach seems logical and has been associated with a lower risk of neonatal respiratory distress syndrome. The choice of immediate delivery is associated with reduced risk of small-for-gestational age babies in case of severe preeclampsia and reduced risk of severe renal impairment in case of mild preeclampsia [64]. Regarding maternal outcomes, immediate delivery in nonsevere preeclampsia offers lower risk of adverse event by 14% and intensive care cost unit by 23%, at the period of late prematurity [65].…”
Section: Treatment Of Hypertension During Pregnancymentioning
confidence: 99%